Chlorophyll Ratio of Kale (Ipomea reptans Poir.) Which Are Cultivation With Hydroponick And Non Hydroponick - Sintia Delia Syafitri; Resti Fevria (Universitas Negeri Padang, 2021)
Chlorophyll is a pigment that gives a green color to the leaves and stems of a plant. Chlorophyll plays an important role in the process of photosynthesis, besides chlorophyll also contains high antioxidants, anti-inflammatory properties and is a wound healing agent. Chlorophyll is found in green vegetables, especially kale. The leaves and stems of kale contain lots of vitamins, protein, calcium, phosphorus, sitosterol and minerals, especially iron which are useful for the growth and health of the human body. Water spinach has many benefits in overcoming constipation, preventing anemia, preventing insomnia and other benefits. Water spinach can be grown hydroponically and non-hydroponically. The objectives of this study were: to determine the chlorophyll content of kale plants cultivated hydroponically and non-hydroponically. This research was conducted at the Wire House of the Biology Laboratory of Padang State University in January-March 2020. This research is a descriptive study. The analysis was carried out: chlorophyll content of kale. Hydroponic kale samples were obtained from the West Sumatra Hydroponic Community in Alai Padang, while the non-hydroponic samples were purchased at Pasar Raya Padang, the analysis of vitamin C content was carried out by the Spectrophotometric Method. From the research that has been done, it is found that the average content of chlorophyll content in hydroponic cultivated kale is 12.21 mg/L and non-hydroponic 12.34 mg/L. The conclusion of the research results is that the chlorophyll content of kale cultivated by hydroponics is lower than that of water spinach cultivated non-hydroponically.